Normal saccadic response using video head impulse test (vHIT) in healthy young adults - Omar, Amira; Jamaluddin, Saiful Adli (Kulliyyah of Allied Health Sciences, IIUM, 2018)
Vertigo and dizziness are common symptoms reported in audiology and ENT clinics. One of the objective assessments includes the video head impulse test (vHIT) where gain & velocity responses of eye movements relative to the head movements were recorded using an infrared camera.